RnD model ADDIE sebagai metode pengembangan Virtual Tour 360 Istana Siak Sri Indrapura - Fadhillah, Rizki Rahmali; Putra, Zetra Hainul; Hermita, Neni; Copriady, Jimmy (Innovative: Journal Of Social Science Research, 2025)
Research and Development (RnD) is a systematic approach tocreating and developing educational products based on the actualneeds in the field. One of the most widely used models in R&D development is the ADDIE instructional design model, whichconsists of five main stages: Analysis, Design, Development, Implementation, and Evaluation. This article comprehensivelydiscusses the basic theory, advantages, disadvantages, andapplication of the ADDIE model in the context of formal and non-formal education development. Through several reviews ofvarious national and international studies, it can be found thatthe ADDIE model is very effective in improving the quality oflearning, integrating technology, and is relevant to variousaspects, including for students with special needs and vocationaleducation. With a highly flexible and evaluative structure, ADDIE has become one of the leading models in the systematic, efficient, and adaptive design of educational products in response to thedevelopment of time and technology.